Implementasi Model Number Heads Together dengan Pendekatan Contextual Teaching and Learning pada Pembelajaran Kimia Kelas IX SMP Cita Hati Surabaya - Haposan Januari Silalahi; Amy Iwani; Saparso Saparso (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to improve student’s understanding and learning activities in chemistry for grade IX at SMP Cita Hati Surabaya through Number Heads Together (NHT) learning model with a Contextual Teaching and Learning (CTL) approach. The research subjects consisted of 23 students from class IX-C, including 12 males and 11 females. This research is a Classroom Action Research (CAR) consisting of 1 pre-cycle and 2 cycles. Data collection instruments include observation sheets and learning outcome test sheets. Data analysis uses Likert scale and explains the percentage of data for each cycle qualitatively. Based on observation sheets, student learning activities increased from cycle 1 to cycle 2. The pre-cycle pre-test results had an average score of 26.09 or 78.26%. The study continued with NHT model with CTL approach, showing an increase in cycle 1 with an average score of 62.60, with 10 students or 43.48% achieving the minimum mastery criterion (KKM). In cycle 2, the majority of students achieved mastery with an average score of 91.30; only 21.74% were in Fair category. These results conclude that the model of NHT with CTL approach effectively makes students being active and improves the understanding of class IX-C at SMP Cita Hati Surabaya.